Business Actors Liability to Consumers of Beverages and Food Containing Liquid Nitrogen - Maharani, Sri; Anggriawan, teddy Prima (Fakultas Hukum Universitas Widya Mataram, 2023)
Technological advances that are developing at this time do not only occur in telecommunication equipment and transportation equipment, but also develop in the food and beverage sector. Where in the near future, food and drinks that can emit smoke have been circulating . Foods and drinks that emit smoke contain liquid nitrogen. However, it is very unfortunate that these food and beverage trends have not been accompanied by the knowledge of business actors and consumers whether these nitrogen-containing foods and beverages are safe for consumption or not. Based on the description of the background above, several problem formulations can be drawn as follows: What are the criteria for drinks and food containing liquid nitrogen consumed by consumers according to the Law on Food Safety and Food Standards? And what is the liability of business actors towards consumers who drink and food containing liquid nitrogen? The type of legal research used in this research is normative juridical (normative legal research method). Liquid nitrogen in food can actually be used as an auxiliary substance. However, if used without adhering to food safety standards, it may cause harm to consumers. This is in accordance with the regulations of the Food and Drug Supervisory Agency (BPOM RI) Number 20 of 2020, liquid nitrogen is used as a processing aid, not a food additive. Liquid nitrogen is used to speed up the process of freezing a product by lowering the very low temperature to minus -200, much lower when using a freezer (around -20 to -40 ) so that liquid nitrogen is very easy to freeze food. If the production process is complete, nitrogen should be removed as much as possible from a product, no residue left. Liability on a contractual basis and unlawful acts in BW, product liability in consumer law is regulated in Article 19 of the UUPK with the burden of proof reversed. The business actor accountability forum is subject to general civil proceedings with the exception of relative competency at the consumer's place of domicile, while compensation in this context is not only in the form of returning goods and demands for reductions or price discounts as in the contractual, or limited to compensation for economic losses as an unlawful act, but also includes compensation for actual damages.